(untitled) (Experimental biology, 2009)
The nonspecific esterases activity in lymph and fatbody of locusts L. migratoria L. during fungi infection B. bassiana has been studied. We found that lethal dose of fungi (LD80) enhances detoxification enzymes activity in lymph and fatbody of locusts at third day after inoculation by fungi. Also have been shown the increase of nonspecific esterases activity in lymph and fatbody of infected locusts at third day. During the "acute" period of infection at sixth day of enzymes activity. The enhanced detoxification system enzymes activity during early stage of fungi infection may be evidence the participation these enzymes in defensive reactions against fungi pathogens.